Edukasi Keselamatan dan Kesehatan Kerja terhadap Peningkatan Pengetahuan Nelayan Suku Mbojo di Desa Belo Kabupaten Bima - Haris, Abdul (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
Occupational Safety and Health (K3) Education for Fishermen. The purpose of this community service activity is to increase the knowledge and awareness of Mbojo fishermen in Belo Village, Bima Regency, regarding occupational safety and health (K3).This study used a pre-test and post-test design involving 30 fishermen as respondents to measure the efficacy of the educational intervention. The educational materials included an introduction to occupational risks, accident prevention techniques, the use of Personal Protective Equipment (PPE), and first aid for work accidents. The results showed a significant increase in participants’ knowledge, skills, and attitudes, with the average pre-test score for OHS knowledge increasing from 55 to 85. Furthermore, the practice of using PPE also increased by 63.64%. The evaluation of the activity showed high enthusiasm from participants and success in understanding first aid skills, which increased from 60 to 95. Concluded to have successfully increased fishermen’s awareness, knowledge, and skills regarding safe work practices. It is recommended that occupational safety and health (OSH) training be conducted continuously with the support of government policies and collaboration among academics, local authorities, and fishing.